Mutations of position and performance of local government public officers: An experimental study - Fajar Gustiawaty Dewi (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to evaluate the ambiguity and conflict characteristics of role stress variables capable of mediating a job transfer and official performance. Research methodology: This experimental research was conducted to obtain a causal relationship between the respondents in Lampung, Way Kanan Regency, and analyzed using the Anova method. Results: The results showed that officials' performance was significantly higher when experiencing low ambiguity, according to role and contingency theories. Furthermore, both attributes were lower when officials received high-frequency and did not mediate the relationship between job transfer and performance. Limitations: This research is limited to paper and pencil, which prevents participants from feeling the real situation. Contribution: This research implies that job transfers can be conducted according to the needs and conditions of the local government.